Cardiac sequelae after coronavirus disease 2019 recovery: a systematic review. (September 2021) - Ramadan, Mohammad Said; Bertolino, Lorenzo; Zampino, Rosa; Durante-Mangoni, Emanuele; ,; Durante-Mangoni, Emanuele; Iossa, Domenico; Bertolino, Lorenzo; Ursi, Maria Paola; D'Amico, Fabiana; Karruli, Arta; Ramadan, Mohammad; et al.
Abstract: Background: Coronavirus disease 2019 (COVID-19) has been implicated in a wide spectrum of cardiac manifestations following the acute phase of the disease. Objectives: To assess the range of cardiac sequelae after COVID-19 recovery. Data sources: PubMed, Embase, Scopus (inception through 17 February 2021) and Google scholar (2019 through 17 February 2021). Study eligibility criteria: Prospective and retrospective studies, case reports and case series. Participants: Adult patients assessed for cardiac manifestations after COVID-19 recovery. Exposure: Severe acute respiratory syndrome coronavirus 2 infection diagnosed by PCR. Methods: Systematic review. Results: Thirty-five studies (fifteen prospective cohort, seven case reports, five cross-sectional, four case series, three retrospective cohort and one ambidirectional cohort) evaluating cardiac sequelae in 52 609 patients were included. Twenty-nine studies used objective cardiac assessments, mostly cardiac magnetic resonance imaging (CMR) in 16 studies, echocardiography in 15, electrocardiography (ECG) in 16 and cardiac biomarkers in 18. Most studies had a fair risk of bias. The median time from diagnosis/recovery to cardiac assessment was 48 days (1–180 days). Common short-term cardiac abnormalities (<3 months) included increased T1 (proportion: 30%), T2 (16%), pericardial effusion (15%) and late gadolinium enhancement (11%) on CMR, with symptoms such as chest pain (25%) and dyspnoea (36%). In the medium term (3–6 months), common changes included reduced left ventricular global longitudinal strain (30%) and late gadolinium enhancement (10%) on CMR, diastolic dysfunction (40%) on echocardiography and elevated N-terminal proB-type natriuretic peptide (18%). In addition, COVID-19 survivors had higher risk (risk ratio 3; 95% CI 2.7–3.2) of developing heart failure, arrythmias and myocardial infarction. Conclusions: COVID-19 appears to be associated with persistent/ de novo cardiac injury after recovery, particularly subclinical myocardial injury in the earlier phase and diastolic dysfunction later. Larger well-designed and controlled studies with baseline assessments are needed to better measure the extent of cardiac injury and its clinical impact.